توظيف المواد الأصيلة في تعليم اللغة العربية لأغراض خاصة: تحديات وحلول - Anuar, Anis Azrina (SIBAWAYH Arabic Language and Education, 2025)
الملخصهدفت هذه الدراسة إلى الكشف عن التحديات التي تواجه توظيف المواد الأصيلة في تعليم اللغة العربية لأغراض خاصة واقتراح حلول عملية لتمكين استخدامها في تطوير الكفاءة التواصلية لدى المتعلمين. اعتمدت الدراسة على المنهج الوصفي التحليلي، حيث تم تحليل الأدبيات والدراسات السابقة ذات الصلة، إضافة إلى الاستفادة من تجربة الباحثة في تدريس مقرر "العربية في مكان العمل" بالجامعة الإسلامية العالمية بماليزيا. وقد توصلت الدراسة إلى أن أبرز التحديات تكمن في: ندرة المواد الأصيلة المناسبة للمجالات المهنية، ضعف مهارات المعلمين في توظيفها، اختلاف مستويات وقدرات الطلبة اللغوية، صعوبة مقروئية النصوص الأصيلة، وطغيان العامية على المواد المرئية والمسموعة، فضلاً عن محدودية تمثيل البيئة الواقعية في بعض المواد المصممة. واقترحت الدراسة ثلاث آليات أساسية لمعالجة هذه التحديات، هي: توفير برامج تدريبية متخصصة للمعلمين، اعتماد استراتيجيات التعلم التعاوني في الصفوف الدراسية، وبناء علاقات تبادلية مع المؤسسات المهنية لتوفير مواد أصيلة عالية الجودة. وتبرز أهمية هذه النتائج في كونها تقدم إطارًا عمليًا يمكن أن يسهم في تحسين جودة تعليم اللغة العربية لأغراض خاصة وتعزيز دافعية المتعلمين نحو ممارسة اللغة في مواقف حقيقية.الكلمات المفتاحية: المواد الأصيلة، التحديات المرتبطة، الحلول المقترحة Abstract This study aims to identify the challenges associated with employing authentic materials in teaching Arabic for Specific Purposes (ASP) and to propose practical solutions to enhance their use in developing learners’ communicative competence. The study adopted a descriptive-analytical approach, analyzing relevant literature and previous studies, in addition to drawing on the researcher’s experience in teaching the course “Arabic in the Workplace” at an International Islamic University. The findings reveal several key challenges, including the scarcity of suitable authentic materials for professional domains, teachers’ limited skills in integrating such materials, learners’ varying language proficiency levels, the low readability of authentic texts, the prevalence of colloquial Arabic in audiovisual materials, and the limited representation of real-world contexts in some designed materials. To address these issues, the study proposes three key strategies: providing specialized teacher training programs, implementing cooperative learning strategies in classrooms, and establishing partnerships with professional institutions to obtain high-quality authentic materials. The significance of these findings lies in offering a practical framework that can improve the quality of ASP instruction and foster learners’ motivation to use Arabic in real-life situations.Keywords: Authentic materials, challenges, solutions